BEBERAPA SIFAT FISIS DAN KIMIA BRIKET ARANG DARI LIMBAH ARANG AKTIF - Gustan Pari; Djeni Hendra; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1990)
The result of  a study on briqueting charcoal from activated charcoal residue,  prepared  by using the hydraulic  press process is presented  in this paper. The residue :  was subjected to two different treatments, namely unwashed  and  washed with  water.  Following   the  treatment, each residue  material  was mixed  with  starch adhesive, using four different concentrations:  0 percent, 1 percent, 2 percent  and 3 percent,  consecutively.The  respons  evaluated from the  briquetted charcoal are the  moisture content, ash content, volatile matter, fixed carbon, density, crushing strength and calorific value. The result shows  that  moisture  content ranges from  3,36 - 5,56 percent, ash content  from  8,06  - 12,78 percent, volatile matter from  23,56 - 41,28 percent, fixed carbon from  45,9 - 68,38  percent, density from 0,6471-0,7985 gr/cm, crushing strength from 0,79 - 6,33 kg/cm and  the  calorific values ranged from 5243,25  -  6378,84  cal/gr.